From Weight Loss to Bedroom Gains: A Case Report on Bariatric Surgery Resolving Erectile Dysfunction - Hasnan, Mohd Ashraff; Mohd Noor, Norhayati; Ismail, Shaiful Bahari; Zainudin, Aida Maziha (IIUM Medical Journal Malaysia, 2025)
This case involves a 59-year-old Malay man who struggled with erectile dysfunction (ED) due to his poorly controlled underlying health conditions for about two years. Despite long-term management for diabetes, hypertension, and dyslipidemia, his weight gain and worsening sugar control affected his ability to maintain an erection during sexual activity. He tried various medications and treatments, including traditional remedies and oral drugs like Kamagra, with little success. Eventually, he underwent bariatric surgery, which led to improvements in his ED, along with better control of other health issues. Psychological factors, like stress and desperation, also played a significant role in his journey, highlighting the importance of holistic care and proper management of both physical and mental health in addressing er ED ectile dysfunction. This case underscores the potential benefits of bariatric surgery in obese patients with ED and emphasizes the need for comprehensive healthcare approaches to manage these complex issues effectively.